Studi Etnobotani Sayuran Lokal Khas Rawa di Pasar Martapura Kalimantan Selatan - Hilda Susanti (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2015)
An ethnobotanical survey through the traders was conducted using a structured questionnaire about the swamp indigenous vegetables that consumed by people and available at Martapura traditional market of South Kalimantan on August 2014. The survey is a part of the research about swamp indigenous vegetables from South Kalimantan that potential as medicinal plant and can be cultivated. The results show the avalaible swamp indigenous vegetables at Martapura traditional market were genjer (Limnocharis flava), kangkung air (Ipomoea aquatica), kalakai (Stechnolaena palustris), supan-supan (Neptunia oleracea), sulur keladi (cocoyam stolon/ Colocasia esculenta), and batang talipuk (Nymphae pubescens Willd). Several Informations about the vegetables were recorded from survey also revealed habitat, harvest practice, edible organ, continuity of availability on market, and processing/comsumption technique. All the respondents were not know about the function of vegetables for the healthy of human.